PENERAPAN KOMUNIKASI EDUKATIF UNTUK PROMOSI BUDAYA KULINER WINGKO TUGU MUDA DI CFD KOTA SEMARANG - Syahputra, Arfan Rahardian; Salwa Diajeng Marhendra; Alifian Sandi Nugroho; Ghania Rifqa Danish Ara; Risanti Vani Fadilla; Arif Hidayat; Ayang Fitrianti (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This study examines the application of educational communication strategies in the promotion of traditional culinary culture of Wingko Tugu Muda at Car Free Day (CFD) events in Semarang City. The research objective is to analyze the effectiveness of interactive and informative communication media such as posters, animated videos that can be accessed through QR codes, and natural interactive games to increase public awareness and appreciation of local culinary heritage. Using a qualitative case study approach, data was collected through participatory observation and digital attendance logging of 63 visitors, as well as product distribution through pre-order and free distribution. The results showed that educational communication supported by digital technology and interactive activities significantly increased visitors' knowledge and interest in Wingko Babat. All 70 product boxes, including modern variants with chocolate glaze and new flavors, were successfully distributed, indicating high public enthusiasm. In conclusion, educational communication strategies combined with product innovation and digital media proved effective in promoting and preserving traditional culinary culture in urban public spaces.